The calculation and comparison of the Detrusor Contractility Parameter and Watts Factor. Issue 8 (4th July 2018) - Gammie, Andrew; Kitney, Darryl; Drake, Marcus; Abrams, Paul; Fry, Chris
Abstract : Aims: To test the significance of association between a validated index of detrusor contractility, v CE, the Watts Factor, and the Detrusor Contractility Parameter, t 20‐80 ; and to test whether t 20‐80 depends on outflow tract resistance as indicated by Bladder Outlet Obstruction Index (BOOI). Methods: Thirty‐seven pressure‐flow traces from 20 male and 17 female patients were analyzed and forms of the Watts Factor, t 20‐80 and BOOI were compared with v CE . Results: The Detrusor Contractility Parameter, t 20‐80, is significantly associated with v CE for both women and men without a high degree of bladder outlet obstruction. The Watts Factor only had a significant association with v CE at the point of maximum flow in women. Conclusions: The Detrusor Contractility Parameter (DCP) ( t 20‐80 ), can be measured easily from the pressure flow curves of a urodynamic test. The Watts Factor at maximum urine flow, WFQmax, can be readily calculated, but is only applicable to women. In both women and men without a high degree of bladder outlet obstruction, DCP is better associated with true detrusor contractility than any Watts Factor analysis.